G110(P) Right on time: Improving time to transfusion in a paediatric haemato-oncology unit. (24th May 2017) - Bruce, G; Coyle, S; Cameron, D; Sweeney, C; Harrison, E
Abstract : Aims: Following relocation of a children's hospital to a combined site supported by a large separate laboratory servicing adults and children, the paediatric haemato-oncology unit perceived significant delays in blood product delivery. As adverse transfusion reactions disproportionately affect children, our audit aims to reduce out of hours transfusion through ward discussion and planning. Methods: Transfusions were identified across two periods (16/6/ 15–30/6/15, 21/9/15–5/10/15) and times were collected for each stage of every transfusion. Results presented departmentally suggested the following: Checking FBC results early during ward rounds to identify necessary transfusions Postponing routine out-of-hours transfusions to the following day A further cycle was carried out (22/9/16–5/10/16). Results: 12 transfusions were identified in each of the first two cycles, 24 in the third. 58% were initiated after 5 pm in the first cycle, 42% in the second and 42% in the third. In the first two cycles no transfusions were postponed to the following day versus 17% in the third cycle. The mean interval between 'FBC resulted' and 'xmatch received' for same day transfusions was 04:58, 02:08, and 03:10 respectively. The mean interval between 'xmatch received' and 'transfusion initiated' for same day transfusions was 04:05, 03:56 and 04:23 respectively. There was a persisting mean interval of around two hours between 'xmatch issued' and 'products leave lab'. Conclusion: Between the first and subsequent audit cycles there were reduced out of hours transfusion rates. Although longer in the third than in the second cycle, there is an improvement in mean interval between 'FBC resulted' to 'xmatch received', attributable to earlier assessment of FBC results. Persisting intervals between 'xmatch issued' and 'products leave lab' are attributable to the fact that laboratory staff cannot alert the ward to blood availability, demanding regular computer checks by staff that can be sidelined by other priorities. Reducing unnecessary out of hours transfusion therefore requires continued focus on rational postponement and early FBC checking in addition to a coordinated effort by staff to regularly check blood availability and request delivery as soon as possible.